Short-term outcomes in older patients with peritoneal malignancy treated with cytoreductive surgery and HIPEC: Experience with 245 patients from a national centre. Issue 9 (September 2021) - Keyes, Alan Martin; Kelly, Michael Eamon; McInerney, Niall; Khan, Mohammad Faraz; Bolger, Jarlath Christopher; McCormack, Emilie; Grundy, Josh; McCormack, Orla; MacHale, John; Conneely, John; Brennan, Donal; Cahill, Ronan; et al.
Abstract: Background: Cytoreductive Surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) is increasingly accepted as the optimal management of selected patients with peritoneal malignancy. There is limited published evidence on outcomes in older patients treated by this complex therapeutic strategy. Methods: A retrospective review of a prospective database of all patients who underwent CRS with HIPEC in a single institution over seven years. A comparative analysis of outcomes in patients under 65 undergoing CRS and HIPEC with patients ≥65 years was performed. The key endpoints were morbidity, mortality, reintervention rate and length of stay in the high dependency/intensive care (HDU/ICU) units. Results: Overall, 245 patients underwent CRS and HIPEC during the study period, with 76/245 (31%) ≥65 years at the time of intervention. Tumour burden measured by the peritoneal carcinomatosis index (PCI) score was a median of 11 for both groups. Median length of hospital stay in the ≥65-year-old group was 14.5 days versus 13 days in the <65-year-old group (∗p = 0.01). Patients aged ≥65-years spent a median of one more day in the critical care unit ∗(p = 0.001). Significant morbidity (Clavien-Dindo ≥ Grade IIIa) was higher in the ≥65-year than the <65-year group (18.4% versus 11.2%). There were no perioperative deaths in the ≥65-year group. Conclusion: This study demonstrates higher perioperative major morbidity in ≥65-year group, but with low mortality in patients undergoing CRS/HIPEC for disseminated intraperitoneal malignancy. This increased morbidity does not translate into higher rates of re-interventions and highlights the importance of optimal patient selection.